2009
DOI: 10.1063/1.3268460
|View full text |Cite
|
Sign up to set email alerts
|

Phase transition of Zn2SnO4 nanowires under high pressure

Abstract: In situ high-pressure angle dispersive x-ray diffraction experiments using synchrotron radiation on inverse spinel structure Zn2SnO4 nanowires were carried out with a diamond anvil cell at room temperature. The crystal symmetry becomes lower at around 12.9 GPa and an intermediate phase with an orthorhombic structure occurs. At about 32.7 GPa, a phase transition occurs accompanying a high-pressure phase. In situ Raman scattering investigation was also performed to explore the phase transition. In the pressure r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 25 publications
10
24
0
Order By: Relevance
“…On the one hand, the pseudo-Voigt deconvolution also reported in Figure 4 shows that the broad band at 560 cm -1 arises from the superimposition of three different contributions at 505, 555 and 666 cm -1 , associated to the B 1u mode of SnO 2 [18] and to the F 2g (3) and A 1g modes of spinel-type Zn 2 SnO 4 [19], respectively. On the other hand, the signal at 330 cm -1 is associated to the E 2 (high)-E 2 (low) mode of ZnO [20], as also pointed out in Figure 4.…”
Section: Resultsmentioning
confidence: 85%
“…On the one hand, the pseudo-Voigt deconvolution also reported in Figure 4 shows that the broad band at 560 cm -1 arises from the superimposition of three different contributions at 505, 555 and 666 cm -1 , associated to the B 1u mode of SnO 2 [18] and to the F 2g (3) and A 1g modes of spinel-type Zn 2 SnO 4 [19], respectively. On the other hand, the signal at 330 cm -1 is associated to the E 2 (high)-E 2 (low) mode of ZnO [20], as also pointed out in Figure 4.…”
Section: Resultsmentioning
confidence: 85%
“…In order to further confirmation, we have recorded micro-Raman spectrum of Zn 2 SnO 4 -700 sample (Figure 3). The strong Raman shift peaks at 669.1(A1g), 530.2(F2g)and 435.85(Eg) cm −1 corresponding to well-known Zn 2 SnO 4 peaks252829. No additional secondary phase of ZnO is observed.…”
Section: Resultsmentioning
confidence: 86%
“…High pressure studies on ZTO nanowires showed that cubic ZTO transformed into an intermediate orthorhombic phase at 12.9 GPa and then to a new high-pressure orthorhombic structure at approximately 32.7 GPa. The structure of the high-pressure phase is similar to the ambient-pressure CaFe 2 O 4 (ferrite-type) structure14. In sharp contrast, theoretical simulations show that at above 39.0 GPa, ZTO transforms into another new orthorhombic structure that is similar to that of titanite-type CaTi 2 O 4 15.…”
mentioning
confidence: 64%